¿Qué leen los profesores de la Universidad de Sonora? Un estudio sobre la lectura como práctica cultural en profesores (2010)
This article is derived from the results of research conducted to describe the cultural dispositions of teachers, based on computer concepts sociological theory of Pierre Bourdieu. In this work, specifically, touch on their reading teachers, as a determining factor in the acquisition of cultural capital. Through a qualitative approach, were interviewed full-time faculty at the University of Sonora, to consider them as the main subject in the restructuring of cultural dispositions of college players. The aim is to know what is the link between reading and teachers, as a provision that forms the habitus of individuals.